ТВОРЧЕСКИЙ ХАРАКТЕР НЕТРАДИЦИОННЫХ УРОКОВ - Абдуллаева, Р.А.; Джуманиязова, Н.А. (SCIENCE and SOCIETY, 2016)
The article deals with the study of non-traditional forms of lessons in foreign languages at school. There are the following non-traditional forms of a lesson: lesson-seminars, lectures, contests, travels, intergrated lesson, lesson-conferences, debates and thematic game lessons. They are effective and promote to better coping with the curriculum material.
Keywords: creative work; effective activity; non-traditional methods; socio-cultural competency; development of a person; individual intellectual qualities